Systematic review of craniofacial osteosarcoma regarding different clinical, therapeutic and prognostic parameters - Weber, Verena; Stigler, Robert; Lutz, Rainer; Kesting, Marco; Weber, Manuel (Frontiers in Oncology, 2023)
BACKGROUND: Osteosarcomas are the most common primary bone tumor while occurrence in the craniofacial skeleton is relatively rare. There are clinical differences of osteosarcomas regarding their location. In this regard craniofacial osteosarcomas (COS) have special characteristics. Extracranial osteosarcomas (EOS) occur mainly in the long bones of the extremities (tibia, humerus and femur). These tumors metastasize hematogenically at a very early stage. In comparison, COS are mainly localized in the mandible and maxilla, occur later in life and show significantly less and later metastasis and respond differently to adjuvant therapy. In the literature, clinical characteristics of COS and EOS are rarely compared directly. The aim of this systematic review is to answer the question whether COS and EOS exhibit fundamentally different biological and clinical behavior and how they differ in terms of survival rates and response to different therapies. METHODS: A systemic review was performed. Pubmed, Cochrane and Google Scholar were used as search engines. The literature research was done by using clearly defined terms and their links. 117 full texts were selected and evaluated for this review. The inclusion criteria were determined using the PICO model. RESULTS: COS have significantly better survival rates, especially if they are located in the jawbone. Surgical R0 resection is crucial for therapeutic success. The study situation regarding the benefit of neoadjuvant chemotherapy in COS is very inhomogeneous. There is also no evidence for the benefit of adjuvant radio- or chemotherapy in COS. The large heterogeneity of the studies in terms of therapeutic concept, initial situation of the patients and outcome considered, as well as the small number of patients with craniofacial osteosarcoma were limiting factors. CONCLUSION: The results of this study show the clear therapeutic and prognostic differences between COS and EOS and underline the necessity to consider both types of osteosarcoma as independent tumor entities in future studies. Furthermore, the study highlights the importance of surgical R0 resection for the prognosis of COS patients. There is no evidence for therapeutic benefit of adjuvant/neoadjuvant radio-/chemotherapy in R0 resected COS cases.